Advances in Chemically Powered Micro/Nanorobots for Biological Applications: A Review. (26th October 2022) - Feng, Ying; An, Miao; Liu, Yang; Sarwar, Muhammad Tariq; Yang, Huaming
Abstract: Micro/nanorobots (MNRs) are capable of autonomous motion, breaking through the limitations of traditional passive transport of nanocarriers. Among them, chemically driven MNRs are the earliest MNRs studied and have received extensive attention from researchers. This review first focuses on the material properties, preparation, driving forms, and mechanisms of chemically driven MNRs. The current status of research on chemically driven MNRs in biomedicine is summarized for various biological applications (drug delivery, diagnostics, anti‐inflammatory, antibacterial, and disease treatment). In terms of biosafety, possible safety issues are analyzed in the context of chemically driven microrobotic applications in terms of three aspects: component characteristics, chemical engines and biological environment. Finally, the challenges and possible future directions of chemically driven MNRs are presented. Abstract : The material characteristics, preparation methods, motion behaviors, and driving mechanisms of chemically driven micro/nanorobots (MNRs) are summarized in this review. A summary of current developments in chemically driven MNRs research is provided from the perspectives of drug delivery, disease diagnosis, anti‐inflammatory, antibacterial, gastrointestinal therapy, and cancer therapy. The MNRs' biosafety characteristics for biological applications are outlined.